HANDLING INDONESIAN-ENGLISH CODE-SWITCHING IN SPEECH RECOGNITION SYSTEMS USING A MACHINE SPEECH CHAIN APPROACH - Vaza Man Tazakka, Rais
There is a phenomenon known as code-switching in human conversations, which is the switching of languages from one language to another during a communication process. In Indonesia, there is a code-switching phenomenon between Indonesian and English. Code-switching phenomenon needs to be addressed in a speech recognition system. Most research on handling code-switching in speech recognition systems use a supervised approach, which relies only on labeled data for training, even though unlabeled data is more readily available. On the other